2008
DOI: 10.1637/8054-070607-reg
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Infectious Laryngotracheitis Virus (ILTV) Isolates from Commercial Poultry by Polymerase Chain Reaction and Restriction Fragment Length Polymorphism (PCR-RFLP)

Abstract: Infectious laryngotracheitis (ILT) is a highly contagious, acute respiratory disease of chickens, of worldwide distribution, that affects growth and egg production and leads to significant economic losses during periodic outbreaks of the disease. Live attenuated vaccines (chicken embryo origin [CEO] and tissue-culture origin [TCO]) have been widely used to control the disease in the United States. It is believed that most of the outbreaks in the United States are caused by vaccine-related isolates that persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 19 publications
2
34
0
4
Order By: Relevance
“…A number of previous studies demonstrated that many ILTV strains circulating in the fields were genetically related to the vaccine strains [3,21]. In USA, [23,24] investigated ILTV isolates from commercial poultry that were collected between 1988 and 2007 and observed that most of the ILT outbreaks have caused milder clinical signs and have been associated with the vaccine-like strain virus. In Europe, 104 field isolates were collected during 35 years from eight different countries and it was shown that 98 of these field isolates had the same RFLP patterns as vaccine strains [21].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies demonstrated that many ILTV strains circulating in the fields were genetically related to the vaccine strains [3,21]. In USA, [23,24] investigated ILTV isolates from commercial poultry that were collected between 1988 and 2007 and observed that most of the ILT outbreaks have caused milder clinical signs and have been associated with the vaccine-like strain virus. In Europe, 104 field isolates were collected during 35 years from eight different countries and it was shown that 98 of these field isolates had the same RFLP patterns as vaccine strains [21].…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) amplification of selected genome areas followed by restriction fragment length polymorphism (RFLP), or sequencing of PCR products are widely used. Initially, both PCR-RFLP and sequencing were critical in strain differentiation of GaHV-1 strains from the USA Oldoni et al, 2008), while complete genome comparisons of outbreak-related isolates and vaccine strains allowed further insight into the origin of GaHV-1 US isolates (Garcia et al, 2013). In the USA, the majority of commercial poultry outbreak-related strains are either indistinguishable from or closely related to vaccine strains, while outbreaks caused by wild-type strains occur to a much lesser extent than those attributed to live attenuated vaccine strains (Oldoni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, both PCR-RFLP and sequencing were critical in strain differentiation of GaHV-1 strains from the USA Oldoni et al, 2008), while complete genome comparisons of outbreak-related isolates and vaccine strains allowed further insight into the origin of GaHV-1 US isolates (Garcia et al, 2013). In the USA, the majority of commercial poultry outbreak-related strains are either indistinguishable from or closely related to vaccine strains, while outbreaks caused by wild-type strains occur to a much lesser extent than those attributed to live attenuated vaccine strains (Oldoni et al, 2008). In Australia, the introduction of the European-origin Serva CEO vaccine to a population of birds previously vaccinated with native vaccines SA2 and A20 resulted in the devastating emergence of novel virulent strains responsible for numerous outbreaks of ILT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic characterization of ILTV strains using molecular methods has allowed the differentiation of vaccine and field strains of ILTV (Creelan et al, 2006;Kirkpatrick et al, 2006b;Ojkic et al, 2006;Oldoni & García, 2007;Neff et al, 2008;Oldoni et al, 2008;Callison et al, 2009;Chacó n & Ferreira, 2009;Moreno et al, 2010). Using these techniques, studies from several geographic areas of the world have established that most outbreaks have been caused by vaccine-related ILTV strains (Creelan et al, 2006;Ojkic et al, 2006;Oldoni & García, 2007;Neff et al, 2008;Oldoni et al, 2008;Blacker et al, 2011). This phenomenon has led to the term ''vaccinal laryngotracheitis'' being coined in the USA (DufourZavala, 2008).…”
Section: Introductionmentioning
confidence: 99%